2010
DOI: 10.1002/pssa.201026093
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure characterization of high‐purity aluminum processed by dynamic severe plastic deformation

Abstract: Fine‐grained aluminum (700–1000 nm) was processed by dynamic severe plastic deformation of coarse‐grained (3 mm) pure aluminum (99.999 wt.%). The resulting microstructure was characterized by transmission electron microscopy (TEM) and X‐ray profile analyses. It is observed that the grain size determined by TEM departs from measurements made by X‐ray profile analysis. In the latter case, the average crystallite size determined over the global crystallographic or on the deformation‐induced texture components, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…[25,26] It is observed here that the initial grain boundary structure, even though distorted, is still visible on the periphery of the sample (Figure 2c). The discrepancies between TEM and XRD measurement have been reported [25,38] in the case of metallic materials deformed by SPD routes. In general, a L. Farbaniec et al/High Purity Ultrafine-Grained Nickel non-uniform grain-refinement occurs due to DPD as suggested by EBSD analysis (Figure 2c and d).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…[25,26] It is observed here that the initial grain boundary structure, even though distorted, is still visible on the periphery of the sample (Figure 2c). The discrepancies between TEM and XRD measurement have been reported [25,38] in the case of metallic materials deformed by SPD routes. In general, a L. Farbaniec et al/High Purity Ultrafine-Grained Nickel non-uniform grain-refinement occurs due to DPD as suggested by EBSD analysis (Figure 2c and d).…”
Section: Discussionmentioning
confidence: 66%
“…However, TEM investigations revealed that the difference in the grain sizes and grain-size distributions along the diameter of the impacted disk is small. [25] This can be attributed to a more planar dislocation slip mechanism due to the lower SFE energy for Ni (%130 mJ Á m À2 [36] ) compared to pure Al (166 mJ Á m À2 [37] ) and also to the higher melting point of the former material. Moreover, the actual step size (0.1 mm) used for EBSD analysis also does not take into account the very small grains detected by TEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That led to the anisotropy of microstructure and mechanical properties in the AA6063 drawn tubes. The anisotropy of microstructure and mechanical properties was also observed in the materials processed by the accumulative roll bonding process [16,17], cold rolling [18], hot rolling [19], severe plastic deformation [20], and dynamic severe plastic deformation [21,22]. Figure 6(b) shows the aspect ratios of the grain size observed in the TD-RD and DD-RD samples as function of the CSR.…”
Section: Methodsmentioning
confidence: 83%
“…From the HIP-processed specimens, samples 12 mm in diameter and 21 mm in height were cut and submitted to DPD using a drop mass bench as described in previous studies. [20,21] After impact, the sample was deformed into a disk shape 22.5 mm in diameter and 6 mm in height (Figure 2), corresponding to an axial strain of approximately 1.25. During DPD, the impact velocity decreases gradually with increasing strain down to a zero value.…”
Section: Methodsmentioning
confidence: 99%